Education and Migration in an Asian Context
XI, 190 p. 27 illus., 9 illus. in color.
Keywords: This edited book explores the complex and multifaceted connections between education and migration in an Asian context from multiple perspectives. It features studies from China, Japan, India, the Philippines, Thailand, and Timor-Leste and covers diverse migration and education experiences. These experiences encompass internal and international migration and forced displacement, as well as questions surrounding education such as school choice, education provision and training as human capital; education and social inclusion; and student performance in a post-conflict context. By covering a wide range of questions and situations, the original scholarship in this book reveals how human development concerns and higher rates of movement within and outside of Asian countries operate on multiple levels in a globalized world.